(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2019)
Additive manufacturing technologies have the potential to make an important contribution to the field of personalized medicine. Besides customized implants, drug delivery systems (DDS) should be tailored to the patient’s specific needs. We developed a hybrid additive manufacturing system based on stereolithography and inkjet printing to generate DDS with selectively incorporated depots of active pharmaceutical ingredients (API) to tailor the release kinetics of the API. In this work we report on the successful proof-of-principle of 3D printing of PEGDA specimens containing depots with two different inks.